Phylogenetic analysis of Pristimantis Jiménez de la Espada, 1870, a megadiverse genus of amphibians (Anura, Brachycephaloidea, Craugastoridae) - Rocha, Mariane Targino (2016)
The genus Pristimantis has 500 species of anurans with distribution in northwest South America, specially in the Andes. Due to the large number of species morphologically diverse, the genus was divided in 11 species groups, with 312 species not allocated in any of them. The great number of species not allocated in species groups is due to the lack of morphological characters to better define and diagnose these groups, and because most of the anteriorly recognized groups in the literature of 70, 80 and 90s decades of the last century were not recovered monophyletic in the most recent phylogenetic analyses. The present study aims to perform a phylogenetic analysis of Pristimantis, with phenotypic and genotypic characters, through total evidence with dynamic homology and parsimony. As a result, Pristimantis is not monophyletic and some of its species were reallocated in the genus Tachiramantis. The species groups within Pristimantis were reformulated with proposed diagnosis. In total, 25 species groups are here defined